Mecanismos de boas práticas de tecnologia da informação nas auditorias tributárias das Fazendas Públicas estaduais após a inserção do sistema público de escrituração digital - Dantas, Cantidiano Novais (2021)
To improve information technology (TI) control activities, supervision and tax audit public governmental revenues, farm organs have deployed public Digital Bookkeeping System (SPED), which impacted on the taxpayer's operations, from accounting and Taxes. The objective of this research was to analyze the perceptions of tax auditors as to the best practices framework ISO/IEC 38500 in executions of computerized tax audit of the Secretariat of State Farm of Sergipe, after deploying SPED. The methodology of the research is exploratory in nature, qualitative approach, field and type case study. The data were collected through semistructured interviews, applied with Tax Auditors tributaries of the State of Sergipe, which act by developing audits of State taxes. The data were examined in the light of the analysis of the narrative. The survey results indicate that, in the perception of the Auditors, management, monitoring, measurements, evaluations and the adequacy of TI used in tax audit are partly present in the organ and in evolution for improvements. However, the Auditors emphasize that there are deficiencies in visibility, dissemination, innovation, training and improvement of the possibilities of the applications referred to it and their innovations. On the contributions of the research include the presentation of a model used for research and the fact of reducing the scarce studies on specialties of the ISO/IEC 38500, away thus the studies that establish these standard relations with other TI governance frameworks. The search was limited to only State public organ of the Brazilian Northeast, a fact that suggests the expansion of the investigation to farm other Federative bodies, deepened the theme and, consequently, demonstrating results closest to the reality.